Statin type and cancer outcomes in patients with diabetes type 2 and solid tumors - Alice C Ceacareanu; Shanria D Jolly; George K Nimako; Zachary A. P. Wintrob (Wolters Kluwer Medknow Publications, 2021)
Objective: Type 2 diabetes mellitus (T2DM) affects 10% of Americans and is associated with an increased incidence of cancer. Statins are first-line cholesterol-lowering medications in the treatment of hyperlipidemia. Several studies have demonstrated a relationship between statin use and reduced cancer incidence. We examined the cancer benefits of statin subtypes, with specific attention to disease-free survival (DFS) and overall survival (OS). Methods: This retrospective review included adults with T2DM diagnosed with solid tumors at Roswell Park Cancer Institute in Buffalo, NY, USA (2003-2010). Individuals with gestational diabetes, incomplete records, or diagnosed with rare solid tumors were excluded. Follow-up began at the date of diagnosis and ended with the first confirmed recurrence, death, or loss of contact. Demographics were assessed by Chi-square, Kaplan-Meier survival analyses, and Cox proportional hazards regression. Findings: Overall, 1102 patients met inclusion criteria, 52.1% of the study participants were female, and 578 participants (52.5%) died during the follow-up period which ranged from 0 to 156 months. Hydrophilic statin use was associated with improved DFS at 5-year follow-up (41.0% vs. 36.9%, P = 0.0077) compared to lipophilic statin use. Multivariate regression revealed that hydrophilic statins were associated with improved DFS (hazard ratio [HR]: 0.706, 95% confidence interval [CI]: 0.526-0.947) and OS (HR: 0.685, 95% CI: 0.503-0.934). Pravastatin was associated with improved OS (HR: 0.674, 95% CI: 0.471-0.964). Conclusion: In patients with T2DM and cancer, hydrophilic statins, and pravastatin in particular, are associated with improved DFS as well as OS. Further research examining the cancer-specific effects of hydrophilic and lipophilic statins is needed to better understand their beneficial effects.